Akuntabilitas Dalam Pandangan Sakai Sambayan - Sondang Selida Apryastuti Purba; Ika Kristianti; Jean Stevany Matitaputty (Politeknik Ganesha Medan, 2022)
The determination of the village fund budget that is carried out every year continues to increase and is seen in its management not in line with good village financial management, as evidenced by the discovery of misuse of village funds arising from the lack of accountability in several villages spread across Indonesia. This study aims to see how the role of local wisdom of sakai sambayan in increasing accountability for financial management amidst the diversity of ethnic and religious communities in Rejomulyo Village, Palas sub-district, South Lampung regency. This research is a qualitative research with primary data sources obtained through interviews and documentation with research sources, namely village officials, village consultative bodies, and community leaders in Rejomulyo Village. The research analysis technique used is data reduction, data presentation, and drawing conclusions. The results and discussion in this study indicate that local wisdom of sakai sambayan in Rejomulyo Village can improve the realization of village financial management accountability, this is due to the positive noble values ??of local wisdom of sakai sambayan, namely cooperation, kindness, and upholding the truth that we can live and apply in stages. The stages of village financial management will contain and realize good accountability. The management of village funds in Rejomulyo Village has been carried out in accordance with the applicable rules, namely Permendagri number 20 of 2018 regarding the stages of village financial management including planning, implementation, administration, reporting, and accountability.